The princely court : medieval courts and culture in North-West Europe, 1270-1380 - Vale, M. G. A. (Malcolm Graham Allan) (Oxford University Press, 2001)
"In this new book, Malcolm Vale sets out to recapture the splendour of the court culture of western Europe in the thirteenth and fourteenth centuries. Exploring the century or so between the death of St. Louis and the rise of Burgundian power in the Low Countries, he illuminates a period in the history of princes and court life previously overshadowed by the courts of the dukes of Burgundy. Taking in subjects as diverse as art patronage and gambling, hunting and devotional religion, Malcolm Vale rediscovers a richness and abundance of artistic, literary, and musical life.